Implementasi Penggunaan Jaringan Mitra Untuk Memperluas Distribusi Kacang Sangrai Ewooww - Resya Dwi Marselina; Ikbal Saepul Ramdan; Naila Syafitri; Nani Sumarni; Surya Kurnia Alamsyah; Widi Aulia Lestari; Wilda Jamilah Suryaman; Wanda Fitriana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Micro, small and medium enterprises can have an impact on economic growth and can also contribute greatly to increasing employment opportunities. It's just that there are many challenges that UMKM have to overcome, such as lack of capital; Difficulty in marketing; Tight business competition; Raw material difficulties; Lack of technical production and expertise; Lack of managerial skills; Lack of knowledge in management issues, including in finance and accounting. To help deal with existing challenges, one solution is to build a partnership network as is done by ewooww roasted peanuts. Partnership is cooperation between two or more people who have a business to achieve their goals. The method used in this research is descriptive analysis which collects data by observing and interviewing the owner and CEO of ewooww roasted peanuts. The partnerships undertaken by ewooww roasted peanuts include traditional markets, wholesalers, resellers, bazaars and events, gift shops. All partnerships have benefits, namely helping the ewooww roasted peanut business to expand the market.